A Method for the Statistical Evaluation of Crosstalk Effect Between Three Parallel Conductors - P. T. Trakadas; C. N. Capsalis (Active and Passive Electronic Components)
There are several cases at which, in order to evaluate the crosstalk effect among transmission lines carrying useful signals, there is a need for probabilistic approach. This paper considers the problem of crosstalk estimation between transmission lines consisting of three conductors in a homogeneous surrounding medium, where the distance between the conductors is a random variable described by uniform distribution. The transmission lines are considered as electrically short. A closed-form equation is developed for the statistical distribution of the per-unit-length mutual inductance (lm) and an analytical one is described for the evaluation of the per-unit-length capacitance (cm). Theoretical results are compared with simulated ones for validation purposes.